Facing Uncertainty yet Feeling Confident: Teenage Migrant Girls' Agencies in Upper Secondary School Transitions - Mäkelä Marja-Liisa; Kalalahti Mira (Routledge, Taylor & Francis Group, 2022)
This article concentrates on the transition from comprehensive school to the upper secondary level from the viewpoint of migrant background girls. Emphasis is on understanding the bounded agency and the ways in which gender and family background are expressed in the modalities of the agency. Previous studies show that ethnic minorities have more difficulties in school, and they continue to higher education less frequently than the majority of students. We are interested in the aspirations of migrant background girls (n = 34) concerning their post-comprehensive transition. Our focus is on the experienced agency during the last year of comprehensive school. Our research questions are: What kinds of modalities do migrant background girls use when considering their educational choices? How do these modalities reflect their bounded agency? The study shows that although the experienced agency is universal among the age group, there are specific ethnic and gender connotations.